Sectors That Accepted The Most Going Concern Audit Opinion During The Covid-19 Pandemic - Khairani Shafira; Hanifah Zsalzsalbila; Hasan Ashari (Husnayain Business Review, 2023)
Purpose - This study aims to determine which company sectors have been most affected by the COVID-19 outbreak based on the receipt of going concern audit opinions in the company's financial statements for the current year since the start of the COVID-19 pandemic. Methodology/approach - The research method used is the descriptive qualitative method. The data used is secondary: audit reports in the annual financial statements of all companies listed on the IDX in 2020 and 2021. The analysis was carried out qualitatively based on quantitative data. Result - The study results show that in 2020–2021, industries operating in the Transportation & Logistics and Non-Primary Consumer Goods sectors received the most opinions regarding going concerns. Keywords: Going Concern Audit Opinion, COVID-19 Pandemic, Company Sector on IDX